2019
DOI: 10.3389/fimmu.2018.03107
|View full text |Cite
|
Sign up to set email alerts
|

Combining Radiotherapy With Anti-angiogenic Therapy and Immunotherapy; A Therapeutic Triad for Cancer?

Abstract: Radiotherapy has been used for the treatment of cancer for over a century. Throughout this period, the therapeutic benefit of radiotherapy has continuously progressed due to technical developments and increased insight in the biological mechanisms underlying the cellular responses to irradiation. In order to further improve radiotherapy efficacy, there is a mounting interest in combining radiotherapy with other forms of therapy such as anti-angiogenic therapy or immunotherapy. These strategies provide differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 181 publications
(194 reference statements)
1
70
0
Order By: Relevance
“…In previous studies, we reported the occurrence of EndMT in irradiated tumor and normal tissues after radiation therapy 18,61,82,83 . Radiation-induced EndMT causes fibrotic changes in both tumors and the normal tissue microenvironment, such as in the lungs and heart vessels, which contribute to tumor radioresistance and normal tissue damage, respectively.…”
Section: Endmt In Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we reported the occurrence of EndMT in irradiated tumor and normal tissues after radiation therapy 18,61,82,83 . Radiation-induced EndMT causes fibrotic changes in both tumors and the normal tissue microenvironment, such as in the lungs and heart vessels, which contribute to tumor radioresistance and normal tissue damage, respectively.…”
Section: Endmt In Radiation Therapymentioning
confidence: 99%
“…There is increasing interest in combining radiotherapy with antiangiogenic therapy or immunotherapy to further improve the effectiveness of radiotherapy (Fig. 1) 83 .…”
Section: Radiation-induced Tumor Endmtmentioning
confidence: 99%
“…It has demonstrated that ORR is changing from 39 to 62% for RT in HCC patients with PVTT (12,(22)(23)(24). Although RT alone could achieve a high locoregional tumor control rate, combining systemic treatments with RT seems necessary because of the failure outside the radiation field (12,25). Proper tumor oxygenation is good for enhancing the RT efficacy, so improvement of tumor hypoxia has been explored using antiangiogenic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Single, large ablative doses of radiation may particularly hamper effective antitumour immune responses; thus, focus has been on fractionated radiation regimens and SBRT protocols . SBRT is theoretically less systemically immunosuppressive than conventional radiation, in which patients have circulating lymphocytes that may be irradiated over 5 to 6 weeks .…”
Section: Immunotherapy Approaches For Canine Sarcomasmentioning
confidence: 99%
“…126,156 Single, large ablative doses of radiation may particularly hamper effective antitumour immune responses; thus, focus has been on fractionated radiation regimens and SBRT protocols. 60,157,158 SBRT is theoretically less systemically immunosuppressive than conventional radiation, in which patients have circulating lymphocytes that may be irradiated over 5 to 6 weeks. 60,126 Early studies have demonstrated that immunotherapy and radiation can safely be administered together and may induce responses, [159][160][161][162] but questions remain regarding the optimal timing of systemic treatment with radiation, radiation dose, and tumour volume irradiated.…”
Section: Rt and Immunotherapy For Sarcomasmentioning
confidence: 99%